Liquid prism based refractometer. (18th April 2017) - Wan, Jing; Lu, Yu; Li, Xiang; Zhang, Zhong; Yang, Junqiang; Jiang, Guirong; Hu, Fangren
Abstract: As the room temperature ionic liquid, the liquid crystal and some new liquid materials appear, some of these liquids have high refractive indices over the measurement range (1.30–1.70) of the conventional Abbe refractometer. Here a new refractometer using a liquid prism and the glancing incidence measurement is proposed. It has a simpler structure and a broader measurement range than the Abbe refractometer. The theoretic results indicate that the measurement range of this refractometer is 1.00–3.86 when the vertex angle of the liquid prism is 30°. The experimental results demonstrate the proposed refractometer is viable. This liquid prism based refractometer will have a good applied prospect because it is easy to convert into a product.